SAT0217 Anti- RO/SSA Antibodies in Systemic Sclerosis: Frequency and Clinical Associations in a Monocentric Referral Cohort. (23rd January 2014) - Breda, S.; Codullo, V.; Fusetti, C.; Caporali, R.; Montecucco, C.
Abstract : Background: Systemic Sclerosis (SSc) is an autoimmune connective tissue disease (CTD) characterized by the presence of several autoantibodies that correlate with diagnostic and prognostic aspects of the disease. Besides those autoantibodies (anti-centromere, ACA; anti-topoisomerase I, anti-topo 1) which are specific to SSc, other reactivities shared with other CTDs can be detected whose clinical associations are less investigated. Anti-Ro/SSA antibodies have been associated with sicca syndrome and recently with the occurrence of pulmonary fibrosis and presence of anti-topo I Objectives: To analyse the frequency of anti-Ro/SSA in patients with SSc and to explore their clinical, laboratory and instrumental associations. Methods: After collecting patients' informed consent, all patients included in the cohort of our centre from 2000 who satisfied LeRoy's criteria for SSc were followed according to EUSTAR recommendations. We recorded data about cutaneous involvement (limited, lc, or diffuse cutaneous, dc), modified Rodnan Skin score, Raynaud phenomenon, digital ulcers, gastrointestinal tract (G-I), lung and peripheral vascular involvement (dyspnea with NYHA class, HRCT, Doppler echocardiography) at baseline and during the follow-up. Antinuclear antibodies (ANA) and specific subsets were analysed using standard methods (indirect immunofluorescence and Elia). Statistical evaluation was performed using software SPSS for Mac. Results: Serum samples from 407 patients were analysed: M:F 50:357, mean age at disease onset ± SD was 57.6±3.72yrs, disease duration± SD was 4.6±6.7 yrs, lc:dc 335:61, ANA+ 369 (91%), ACA 195 (48%), anti-topo 83 (20%). Anti-Ro/SSA antibodies were detected in 50 (12%) patients: they were concomitant with ACA in 21/50 (42%) patients, with anti-topo1 in 7/50 (14%), with anti-RNP in 1/50 (2%). In 21/50 (42%) anti-Ro/SSA antibodies were associated with no other specificity. No significant differences between the anti-Ro+ve and anti-Ro-ve group were found for cutaneous or gastrointestinal involvement and presence of Raynaud's phenomenon. At baseline the frequency of significant dyspnea (NYHA≥2) was significantly higher in patients with anti-Ro antibodies (58%vs37%, p=0.03), independently of the presence of anti-topo-1. Accordingly, but with no significant difference, in the anti-Ro+ group there was a higher frequency of HRCT alterations ((honey-combing (HC) and ground glass 28%vs19% and 20%vs16% respectively); % DLCO reduction (-29(-71-+63)%VS-22(-90-+65)%); estimated systolic pulmonary artery pressure on echocardiography (25(18-33)mmHg vs 20 (16-30)mmHg) and % of overlap with Sjögren syndrome (33%vs11%). The same associations were confirmed in patients with anti-Ro antibodies positivity only, with a significantly higher presence of HC at HRCT (64%vs30%, p<0.01) and higher DLCO % reduction (-39(-71-+7)% vs -23(-90-+65)%, p<0.05). After a mean follow up of 9.2±2.6 years, the presence of antiRo/SSA did not influence survival (94% vs 93% in the rest of the cohort). Conclusions: In SSc patients, anti-Ro antibodies are frequent and significantly associated with respiratory symptoms already at disease onset. This correlation supports the utility of anti-Ro in the prognostic stratification of organ involvement, regardless of the presence of other autoantibodies. References: Disclosure of Interest: None Declared